Transfer Pricing dari Perspektif Perencanaan Pajak, Tunneling Incentives, dan Aset Tidak Berwujud - Sartika Wulandari; Rachmawati Meita Oktaviani; Widhian Hardiyanti (Wahana Riset Akuntansi, 2021)
Transactions with related parties are often used by companies to conduct transfer pricing. This study purpose to provide empirical evidence regarding the effect of tax planning, tunnelingsincentives and intangible assets on transfer pricing, either simultaneously or partially. The object of this research is manufacturing companies listed on the Indonesia Stock Exchanges in 2016-2019. The population in this study are manufacturing companies listed on the Indonesian Stock Exchanges for the period 2016-2019. By using purposive sampling technique data obtained 96 companies. Data analysis technique using Eviews. The results show that tax planning and tunneling incentives have an effect on transfer pricing, while intangible assets have no effect on transfer pricing. The results of this study are expected to provide input for future research on transfer pricing. Further research can use other variables such as KAP specialization, percentage of independent commissioners, or proxies to measure other intangible assets, such as research and development costs. For transfer pricing, you can use other proxies, for example by using an index. Keywords: Transfer Pricing; Tax Planning; Tunneling Incentives; Intangible Assets.